2017
DOI: 10.1103/physreve.95.032203
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of chimeras through induced multistability

Abstract: Chimeras, namely coexisting desynchronous and synchronized dynamics, are formed in an ensemble of identically coupled identical chaotic oscillators when the coupling induces multiple stable attractors, and further when the basins of the different attractors are intertwined in a complex manner. When there is coupling-induced multistability, an ensemble of identical chaotic oscillators-with global coupling, or also under the influence of common noise or an external drive (chaotic, periodic, or quasiperiodic)-ine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…3. It should be noted that these attractors are similar to those reported earlier by Ujjwal et al [19], where chimera states in an ensemble of globally coupled Lorenz oscillators were studied. It was proposed that the attractors A 1 and A 2 appear as a result of change in the effective parameters of the system and the effective modulation of symmetric fixed points due to coupling between the oscillators.…”
Section: Coupled Lorenz Systems Near the Hopf Bifurcationsupporting
confidence: 87%
See 1 more Smart Citation
“…3. It should be noted that these attractors are similar to those reported earlier by Ujjwal et al [19], where chimera states in an ensemble of globally coupled Lorenz oscillators were studied. It was proposed that the attractors A 1 and A 2 appear as a result of change in the effective parameters of the system and the effective modulation of symmetric fixed points due to coupling between the oscillators.…”
Section: Coupled Lorenz Systems Near the Hopf Bifurcationsupporting
confidence: 87%
“…Our motivation arises in part from the observation [19] that coupling dynamical systems effectively alters the values of the parameters governing the flows. In addition the coupling can affect the stability of the coupled dynamics and therefore it becomes important to examine the dynamics of coupled systems in the neighbourhood of bifurcations since here fundamentally new phenomena can arise.…”
Section: Introductionmentioning
confidence: 99%
“…Multistability induced by the coupling can also appear in continuous time coupled oscillators 44 . Our results suggest that asymmetric cluster and chimera states may be induced by an external constant uniform field acting on an ensemble of chaotic oscillators.…”
Section: Discussionmentioning
confidence: 99%
“…These states were also studied for a globally coupled network of semiconductor lasers with delayed optical feedback [20]. Recently, it has been shown that the chimera states may emerge as a result of induced multistability due to the couplings that bring the system parameters in a multistable regime [6]. The coupling effectively changes the parameter of the system leading to multistable dynamics and finally the creation of chimera states.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have shown that coupled oscillators should have weak and nonlocal coupling to show chimera states. At other instances it was argued that for globally coupled oscillators chimera states can occur as a result of multistability [5,6]. On changing the coupling parameter the transition to various collective states can be achieved depending upon initial conditions.…”
mentioning
confidence: 99%